Pengaruh Kompensasi, Rotasi Kerja, dan Masa Kerja terhadap Motivasi Kerja dengan Penilaian Kinerja sebagai Moderating pada Unit Sentra Kredit PT. Bank Negara Indonesia (Persero) Tbk., Surabaya - Widya Gunawan, Aries; Fitri Sya’bania, Anisa (IPB University, 2024)
PT. Bank Negara Indonesia (Persero) Tbk., or known as BNI, is one of the state-owned banks with the largest source of income coming from providing credit. So, the credit department or credit center unit has an important role. This important role needs to be supported by various attributes so that the tasks and targets set can be achieved optimally. The attributes referred to include management policies to increase motivation, such as compensation, job rotation, and length of service. This research aims to find out whether compensation, work rotation, and length of service influence work motivation in the credit center unit of PT. Bank Negara Indonesia (Persero) Tbk., Surabaya. The number of samples in this study was 75 respondents. The research method used is quantitative with validity testing, reliability testing, classical assumption testing, multiple regression testing, simultaneous hypothesis testing, coefficient of determination (R2), and Moderated Regression Analysis (MRA). The research results show that compensation has the highest significant influence compared to length of service on motivation. Meanwhile, job rotation does not have a significant effect on motivation.